2019
DOI: 10.1002/ecm.1359
|View full text |Cite
|
Sign up to set email alerts
|

The intrinsic predictability of ecological time series and its potential to guide forecasting

Abstract: Successfully predicting the future states of systems that are complex, stochastic, and potentially chaotic is a major challenge. Model forecasting error (FE) is the usual measure of success; however model predictions provide no insights into the potential for improvement. In short, the realized predictability of a specific model is uninformative about whether the system is inherently predictable or whether the chosen model is a poor match for the system and our observations thereof. Ideally, model proficiency … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
98
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(120 citation statements)
references
References 67 publications
1
98
0
Order By: Relevance
“…During 2013-2015, precipitation falling at the field site exhibited no seasonality (electronic supplementary material, figure S3a), the average annual precipitation at the field site was 916 mm (2012-2015), and maximum annual precipitation registered at the field site in the last 10 years was 1265 mm m −2 . The intrinsic predictability of the total precipitation (natural + supplemental) estimated by permutation entropy [2] was 0.77 in the M-plots, which was equal to the predictability of the natural precipitation of the study site. In L-plots, it was 0.86, and thus, 11.2% lower than that of the M-plots [19].…”
Section: (B) Precipitation-predictability Treatmentmentioning
confidence: 88%
“…During 2013-2015, precipitation falling at the field site exhibited no seasonality (electronic supplementary material, figure S3a), the average annual precipitation at the field site was 916 mm (2012-2015), and maximum annual precipitation registered at the field site in the last 10 years was 1265 mm m −2 . The intrinsic predictability of the total precipitation (natural + supplemental) estimated by permutation entropy [2] was 0.77 in the M-plots, which was equal to the predictability of the natural precipitation of the study site. In L-plots, it was 0.86, and thus, 11.2% lower than that of the M-plots [19].…”
Section: (B) Precipitation-predictability Treatmentmentioning
confidence: 88%
“…In order to study the predictability of diseases in a comparative framework, which also permits stochasticity and model nonstationarity, we employ permutation entropy as a model-free measure of time-series predictability [31][32][33] . This measure, i.e permutation entropy, is ideal because-in addition to being a model independent metric of predictability-recent work has demonstrated that it correlates strongly with known limits to forecasting in dynamical systems, e.g., models where we can measure Lyapunov stability [31][32][33] and can be transformed into an estimate of Kolmogorov-Sinai entropy 34 . Additionally, recent studies by Pennekamp et al 33 and Garland et al 35 demonstrated that permutation entropy correlated strongly with forecast accuracy for ecological models and with anomalies in climatological data.…”
mentioning
confidence: 99%
“…Since its conception, PE has been shown to converge to the Kolmogorov–Sinai entropy [ 15 , 16 ] or the metric entropy [ 29 , 30 ] under a variety of conditions and depending on the features (e.g., stationary, ergodic) of the underlying generating process. It has also been shown to correlate with intrinsic predictability in a variety of time series [ 13 , 14 ]. For the purposes of this paper, we simply view permutation entropy as a measure of the temporal complexity of a time series and we treat abrupt changes in that complexity as a signal of possible anomalies, naturally occurring or data related.…”
Section: Methodsmentioning
confidence: 99%
“…In the context of a time series, this translates to a measure of how information propagates forward temporally. This has implications for predictability [ 13 , 14 ], among other things; indeed, these measures have been shown to converge to the Kolmogorov–Sinai entropy under suitable conditions [ 15 , 16 ], as described in Section 2.2 . The goal here is not to measure the complexity of paleoclimate data in any formal way, however.…”
Section: Introductionmentioning
confidence: 99%